Essential norm estimates for Hankel operators on convex domains in $\mathbb{C}^2$ - Čučković, Željko; Şahutoğlu, Sönmez (Mathematica Scandinavica, 2017)
Let $Ω \subset \mathbb{C}^2$ be a bounded convex domain with $C^1$-smooth boundary and $φ \in C^1(\overline{Ω})$ such that $φ $ is harmonic on the non-trivial disks in the boundary. We estimate the essential norm of the Hankel operator $H_{φ }$ in terms of the $\overline{\partial}$ derivatives of $φ$ “along” the non-trivial disks in the boundary.